Finance and economic growth in OECD and G20 countries - Cournède, Boris (OECD Economics Department Working Papers, 2015)
This paper shows that finance has been a key ingredient of long-term economic growth in OECD and G20 countries over the past half-century, but that there can be too much finance. The evidence indicates that at current levels of household and business credit further expansion slows rather than boosts growth. Causality from more credit to slower growth is supported by a novel empirical methodology which exploits changes in financial regulation across countries and time as a source of exogenous variation in financial size. The empirical analyses point to five factors that link more credit to slower growth: i) excessive financial deregulation, ii) a more pronounced increase in credit issuance by banks than other intermediaries, iii) too-big-to-fail guarantees by the public authorities for large financial institutions, iv) a lower quality of credit and v) a disproportionate rise of household compared with business credit. By contrast, expansions in stock market funding in general boost growth